Anticholinergic medication exposure predicts poor physical capability: Findings from a large prospective cohort study in England. (December 2020) - Yrjana, Kaisa R.; Keevil, Victoria L.; Soiza, Roy L.; Luben, Robert N.; Wareham, Nicholas J.; Khaw, Kay-Tee; Myint, Phyo K.
Highlights: Exposure to anticholinergic medication predicts lower physical capability. Associations were seen in a sample of men and women aged 48–92 years from a general population. Differences in walking speed were equivalent to 3–9 years' difference in age. Exposure to anticholinergic medication is prevalent and potentially modifiable. Identifying modifiable risk factors is necessary to optimise late-life function. Abstract: Objectives: To examine whether anticholinergic medication exposure in middle and late life is associated with physical capability. Study design: We used data from 8477 men and women who had enrolled in the European Prospective Investigation of Cancer-Norfolk study at baseline (1HC; 1993–1997) and who had attended its third health examination (3HC; 2004–2010). Medication history at the 1HC and 3HC was used to score participants according to the Anticholinergic Cognitive Burden (ACB) Scale at baseline and 3HC; participants were categorised as ACB = 0, ACB = 1, ACB> 2. Main outcome measure: At 3HC, physical capability was objectively measured by: usual walking speed, maximum grip strength, timed chair stands speed (TCSS) and standing balance. Linear and logistic regression models examined prospective and cross-sectional associations between ACB and physical capability, controlling for co-morbidity, sociodemographic and lifestyle factors. Results: The analyses included 3386 men and 4110 women who were 56.4 (SD 7.9) and 55.0 (7.7) years old respectively at baseline and 69.4 (8.1) and 67.9 (8.0) years old at follow-up. Significant cross-sectional and prospective relationships were observed for all physical capability measures in women, except grip strength. For example, women with ACB ≥ 2 compared with ACB = 0 at baseline had 0.07 m/s (95 % CI -0.11, -0.03) slower usual walking speed, 2.61 stands/min (-4.17, -1.05) slower TCSS and higher odds of being unable to complete a tandem stand (odds ratio 2.40, 95 % CI 1.53, 3.76). These trends were observed in men but were less consistent in prospective analyses. Conclusion: Exposure to anticholinergic medication predicts poor physical capability and is a potentially reversible risk factor.